2001
DOI: 10.1074/jbc.m100429200
|View full text |Cite
|
Sign up to set email alerts
|

Coupling between Cyclooxygenase, Terminal Prostanoid Synthase, and Phospholipase A2

Abstract: We have recently shown that two distinct prostaglandin (PG) E 2 synthases show preferential functional coupling with upstream cyclooxygenase (COX)-1 and COX-2 in PGE 2 biosynthesis. To investigate whether other lineage-specific PG synthases also show preferential coupling with either COX isozyme, we introduced these enzymes alone or in combination into 293 cells to reconstitute their functional interrelationship. As did the membrane-bound PGE 2 synthase, the perinuclear enzymes thromboxane synthase and PGI 2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
111
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(125 citation statements)
references
References 65 publications
12
111
1
1
Order By: Relevance
“…COX-1 appeared to be distributed rather uniformly throughout the ER membrane, whereas COX-2 was enriched in the perinuclear region. Similar locations of these enzymes were seen in HEK293 cells, as described previously (14,16).…”
Section: Mpges-2 and Pge 2 Productionsupporting
confidence: 51%
“…COX-1 appeared to be distributed rather uniformly throughout the ER membrane, whereas COX-2 was enriched in the perinuclear region. Similar locations of these enzymes were seen in HEK293 cells, as described previously (14,16).…”
Section: Mpges-2 and Pge 2 Productionsupporting
confidence: 51%
“…Previous sketchy studies to focus on individual eicosanoids in EAE or MS patients have obvious limitations, as Ͼ20 different eicosanoids are produced by the concerted actions of cPLA 2 ␣ and downstream enzymes (Fig. S1) (16)(17)(18). To overcome such complexity and some controversy, we evaluated the cascade in the SCs of naive and EAE mice by the nonbiased top-down approach (AA cascade-targeted lipidomics and transcriptomics) and confirmed the results from knockout studies.…”
Section: Studies Of Experimental Autoimmune Encephalomyelitis (Eae) mentioning
confidence: 74%
“…By the AA cascadetargeted lipidomics approach, we found that the PGE 2 pathway is favored and the PGD 2 , PGI 2 , and 5-LO pathways are attenuated. Correlation analysis imply that the AA producing enzyme cPLA 2 ␣ possibly passes more AA to the COX than the 5-LO pathway in EAE, because the sequential actions of eicosanoidsynthesizing enzymes are regulated spatially and temporally in the cells, the so-called functional coupling (16)(17)(18). Likewise, PGH 2 , a common precursor of PGs, appears to be selectively consumed by the PGE 2 pathway rather than the PGI 2 and PGD 2 pathways, thereby producing PGE 2 in the SCs of EAE mice.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, R-flurbiprofen has similar Ab42 lowering activity to S-flurbiprofen, but much less potent COX inhibitory activity. (see for review Tegeder et al 2001b) Because HEK293 cells produce very low prostaglandin E 2 and have negligible activity of the enzymes involved in this cascade (Ueno et al 2001), the prostaglandin E 2 levels in our HEK293 culture were undetectable, although readily measured in CHO cells (data not shown). While we could not confirm the absence of COX inhibition by R-flurbiprofen in HEK293 cells, previous reports show the IC 50 for human COX-1 and COX-2 by R-flurbiprofen are more than 40 lM and 100 lM, while those of S-flurbiprofen are 0.03 lM and 0.9 lM, respectively (Geisslinger et al 2000; see for review Tegeder et al 2001b).…”
Section: Discussionmentioning
confidence: 97%